Detection of prohibited substances in equine hair by ultra‐high performance liquid chromatography–triple quadrupole mass spectrometry – application to doping control samples. Issue 7 (30th March 2018) - Gray, B.; Viljanto, M.; Menzies, E.; Vanhaecke, L.
Abstract: The detection of drugs in human hair samples has been performed by laboratories around the world for many years and the matrix is popular in disciplines, such as workplace drug testing. To date, however, hair has not become a routinely utilised matrix in sports drug detection. The analysis of hair samples offers several potential advantages to doping control laboratories, not least of which are the greatly extended detection window and the ease of sample collection and storage. This article describes the development, validation, and utilisation of a sensitive ultra‐high performance liquid chromatography– triple quadrupole mass spectrometry (UHPLC– MS/MS) method for the detection of 50 compounds. This provides significantly improved coverage for those analytes which would be of particular interest if detected in hair, such as anabolic steroid esters and selective androgen receptor modulators (SARMs). Qualitative validation of the method resulted in estimated limits of detection as low as 0.1 pg/mg for the majority of compounds, with all being detected at 2 pg/mg or below. The suitability of the method for the detection of prohibited substances in incurred material was demonstrated by the successful detection of several compounds, such as stanozolol, boldenone undecylenate, clenbuterol, and GW‐501516, in genuine equine hair samples. Estimated concentrations of the detected substances ranged from 0.27 to 8.6 pg/mg. The method has been shown to be fit‐for‐purpose for routine screening of equine hair samples by the analysis of over 400 genuine hair samples. Abstract : Detection of prohibited substances in equine hair samples for doping control purposes. Demonstration of method suitability by the successful detection of a range of prohibited substances in genuine samples.